USING NLP TO INCREASE MOTIVATION WHEN TEACHING THE RUSSIAN LANGUAGE - Makhmudova D.S. (Web of Journals Publishing, 2025)
Devoted to the study of the use of neurolinguistic programming (NLP) for motivation in the process of teaching Russian as a foreign language. Exploring the use of NLP to improve learning effectiveness. The theoretical foundations of NLP are reviewed, including its history, principles and impact on the development of communication skills
Keywords: neurolinguistics, programming, efficiency, educational process,communication skills, learning process, verbal and non-verbal aspects.